Genetic testing for BRCA1 and BRCA2 in the Province of Ontario. Issue 3 (31st August 2015) - Finch, A.; Wang, M.; Fine, A.; Atri, L.; Khalouei, S.; Pupavac, M.; Rosen, B.; Eisen, A.; Elser, C.; Charames, G.; Metcalfe, K.; Chang, M.C.; et al.
Abstract : In 2001, genetic testing for BRCA1 and BRCA2 was introduced in Ontario, for women at high‐risk of breast or ovarian cancer. To date over 30, 000 individuals have been tested throughout Ontario. Testing was offered to all Ontario residents who were eligible under any of 13 criteria. We report the results of tests conducted at Mount Sinai Hospital from 2007 to 2014. A total of 4726 individuals were tested, 764 (16.2%) were found to carry a pathogenic variant (mutation). Among 3684 women and men who underwent testing without a known familial BRCA mutation, 331 (9.0%) were found to carry a mutation. Among 1042 women and men tested for a known family mutation, 433 (41.6%) were positive. There were 603 female mutation carriers, of these, 303 were affected with breast or ovarian cancer (50%) and 16 with another cancer (2.3%). Of 284 unaffected female carriers, 242 (85%) were tested for a known family mutation and 42 (15%) were the first person in the family to be tested. By placing greater emphasis on recruiting unaffected female relatives of known mutation carriers for testing, greater than one‐half of newly identified carriers will be unaffected.